Irreducible Volar DRUJ Dislocation with Distal Radius Fracture Dislocation - Gulbrandsen, Matthew T.; Putnam, Jill G.; Watson, J. Tracy; McKee, Michael D. (Journal of Wrist Surgery, 2020)
Background Volar dislocations of the distal radioulnar joint (DRUJ) are rare and often missed during initial evaluation. Chronic dislocations and disability can occur when DRUJ dislocations are unrecognized and not reduced. DRUJ dislocations often occur with other wrist injuries, which may complicate reduction. Closed reduction can fail to reduce DRUJ dislocations, in which case open reduction is necessary.Case Description This case describes a patient who had a volar dislocation of the DRUJ with an associated dorsal distal radius fracture dislocation. Initial attempts at closed reduction were unsuccessful which prompted surgical intervention. After open reduction and internal fixation of the distal radius fracture dislocation, closed reduction of the DRUJ remained unsuccessful. This prompted an open reduction of the DRUJ. Surgical exposure demonstrated that the extensor carpi ulnaris and the distal radius had prevented closed reduction of the DRUJ. Postoperatively, a splint was placed with the wrist in supination. The patient followed-up at the 2- and 4-month intervals with persistent subluxation. However, the patient also reported minimal pain and the ability to return to work and previous level of activity.Literature Review Current literature regarding irreducible volar DRUJ dislocations with distal radius fracture dislocations includes sparse case reports, which are reviewed in this report.Clinical Relevance This case illustrates successful treatment for an uncommon volar DRUJ dislocation associated with a dorsal distal radius fracture dislocation and can be utilized to help guide future treatment of similar complex cases.
Keywords: distal radius; DRUJ; dislocation; irreducible